Strengthening Religious Moderation through Multicultural Learning for STAI Ibnurusyd Kotabumi Students in the Digital Era - Yuni Meilina; Yanti Wijaya; Nopi Yanti; Zulkarnain Rakhman; Tinah Tinah; Siti Afifatun (BASICA, 2025)
This study aims to analyze the strengthening of religious moderation through multicultural learning for students at STAI Ibnurusyd Kotabumi in the digital era. This research is motivated by the increasing challenges of intolerance, radicalism, and the spread of unverified religious information through digital media that influence students' mindsets. The research approach uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. Research informants consisted of lecturers and students involved in the multicultural learning process on campus. The results of the study indicate that: first, the implementation of multicultural learning is carried out through the integration of values ​​​​of tolerance, respect for diversity, open dialogue, and the use of digital media in the learning process. Second, supporting factors for strengthening religious moderation include institutional commitment, the role of lecturers, a harmonious academic environment, and the use of digital media as an educational tool. Meanwhile, inhibiting factors are low student digital literacy, the negative influence of social media, and the persistence of exclusive religious understanding. Third, multicultural learning has positive implications for increasing students' attitudes of tolerance and religious moderation. Students become more open to differences, able to think critically about digital information, and develop social awareness in maintaining harmony in a pluralistic society. This research confirms that multicultural learning is an effective strategy for strengthening students' religious moderation in the era of digital transformation.